1924
DOI: 10.1152/ajplegacy.1924.71.1.209
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the Composition of Glomerular Urine, With Particular Reference to the Problem of Reabsorption in the Renal Tubules

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0
1

Year Published

1927
1927
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(38 citation statements)
references
References 0 publications
1
36
0
1
Order By: Relevance
“…The protein concentration in 41 samples of glomerular and proximal tubular fluid from the guinea pig and the rat was found to range from less than 30 mg per 100 ml to less than 200 mg per 100 ml. Earlier, Wearn and Richards (10) had found no protein in 11 frog glomerular samples and concluded that the glomerular filtrate was protein free.…”
mentioning
confidence: 97%
“…The protein concentration in 41 samples of glomerular and proximal tubular fluid from the guinea pig and the rat was found to range from less than 30 mg per 100 ml to less than 200 mg per 100 ml. Earlier, Wearn and Richards (10) had found no protein in 11 frog glomerular samples and concluded that the glomerular filtrate was protein free.…”
mentioning
confidence: 97%
“…Until the 1920s, a debate raged on the mechanism of urine formation. Some researchers championed a filtration doctrine and others ascribed secretory power to both the glomerulus and tubules (11,12). The secretory theory was more popular, however, because the sheer volume of blood that would first need to be filtered and then reabsorbed by the kidney was enormous.…”
Section: The Milieu Intérieur and The Kidney's Essential Rolementioning
confidence: 99%
“…When Wearn and Richards introduced the micropuncture technique to the study of the kidney (first in amphibia, which had large renal structures amenable to manipulation), the debate on the formation of urine was resolved (11,15). By sampling the fluid elaborated from the glomerular capsule of a frog, the team demonstrated a proteinfree filtrate that was otherwise similar to blood.…”
Section: Early Investigations Form the Frameworkmentioning
confidence: 99%
“…73 of Bowman, proved beyond doubt that phenol red is separated from the blood as it passes through the glomerulus (3,4). At the same time, also, direct proof of selective re-absorption in the renal tubule was supplied.…”
Section: Experiments Concerning the Question Of Secretion Of P H T H mentioning
confidence: 96%